Mathematical Insights into Aboge Calendar: Ethnomathematics Study of Javanese Cultural Heritage in Cikakak Village - Kusuma, Anggun Badu; Hanum, Farida; Abadi, Agus Maman (Mathematics Education Journal, 2025)
Traditional calendars often embody complex knowledge systems that remain underexplored in formal academic discourse, especially in the context of indigenous mathematics. This study investigates the mathematical structures embedded in the Javanese Aboge calendar, a traditional timekeeping system preserved by the Aboge community in Cikakak Village, Banyumas Regency, Indonesia. While the official Javanese calendar has transitioned to the Asapon kurup, the Aboge community continues to follow the older Aboge kurup, rooted in local belief and tradition. Using a qualitative descriptive approach and ethnographic methods—comprising field observations, interviews, and collaborative computations—this study examines the underlying mathematical logic of the calendar. The findings reveal that the Aboge calendar applies modular arithmetic, particularly congruences modulo 7 (days) and modulo 5 (pasaran), to determine the first day of each month. These values follow recursive patterns modeled using mathematical formulas. Additionally, the Chinese Remainder Theorem is employed to calculate intervals between specific day-pasaran pairs, validating traditional practices through formal mathematical reasoning. The results demonstrate that the Aboge calendar encapsulates sophisticated mathematical concepts traditionally transmitted through memorization. This study highlights the value of cultural diversity and affirms the role of indigenous knowledge in sustainable development, reinforcing the importance of integrating local traditions into educational and heritage preservation efforts.